The Influence of Psychological Capital and Knowledge Sharing on Organizational Citizenship Behavior (OCB) at PT XYZ - Erviyani, Yulita; Saberina, Sabilla; Puspita, Mugi (Sinergi International Journal of Management and Business, 2025)
This study aims to determine the state of psychological capital, knowledge sharing and organizational citizenship behavior (OCB) and to find the amount of influence of psychological capital and knowledge sharing on organizational citizenship behavior in PT XYZ employees, both partially and simultaneously. The method used in this research is descriptive and verification with a quantitative approach. The population used in this study were all employees of PT XYZ, which amounted to a population of 55 respondents using non-probability sampling techniques, namely saturated sampling of 55 respondents using the Slovin formula. Based on the results obtained that respondents' responses regarding Psychological Capital are included in the sufficient category, Knowledge Sharing is included in the sufficient category and Organizational Citizenship Behavior (OCB) is included in the sufficient category. Based on the results of determination testing, it is found that Psychological Capital has an effect of 0.471 or 47.1% on Organizational Citizenship Behavior (OCB), Knowledge Sharing has an effect of 0.634 or 63.4% on Organizational Citizenship Behavior (OCB), Psychological Capital and Knowledge Sharing have an effect of 0.624 or 62.4% on Organizational Citizenship Behavior (OCB). Based on the results of partial hypothesis testing, it shows that Psychological Capital has no effect on Organizational Citizenship Behavior (OCB), Knowledge Sharing affects Organizational Citizenship Behavior (OCB). Based on the results of hypothesis testing simultaneously Psychological Capital and Knowledge Sharing affect Organizational Citizenship Behavior (OCB).